Pancreatic Temperature During Transport for Transplantation: A Preclinical Study - Paim, Sibele Maria Schuantes; Cruz, Victor Arayama; Gomes, Karoline Sabrina de Carvalho; Araujo, Julia Karini da Silva; Coutinho, Graciana Maria de Moraes; Teraoka, Eliana Cavalari; Leite, Renata Fabiana; Gonçalves, Vanessa Ayres; Carbonel, Adriana Aparecida; Simões, Manuel de Jesus; et al. (Brazilian Journal of Transplantation, 2026)
Objectives: To compare the viability of porcine pancreases transported under static cold conditions using two transport models. Methods: A prospective preclinical case-control study with an adapted design, conducted on Landrace pig organs. Data were collected from three variables: temperature, macroscopic assessment, and histology. The variables were compared using two packaging models: the experimental model, Autonomous and Intelligent Packaging for Cold Chain in Healthcare Systems (Embalagem Autônoma e Inteligente para Cadeia Fria de Sistemas de Saúde [EMAIS-SR]), and the control, a conventional thermal container widely used and filled with ice. Three thermometers were used for temperature measurements: two for internal temperature and one for surface temperature. The macroscopic evaluation analyzed color, tissue integrity, consistency, and the presence of lesions, edema, or hematomas in the organ. For histology, the samples were fixed and stained with hematoxylin-eosin, which allows visualization of tissue morphology under light microscopy, followed by immunohistochemical analysis. Results: Ten experimental surgeries were performed: six pancreases were stored under static cold conditions and transported in the active-cooling container, while four were transported in the conventional ice-filled container. Among all cases, only one pancreas had an exit temperature higher (12.1 °C) than the recommended maximum of 8 °C. However, in the macroscopic evaluation, the organ with the higher exit temperature received a better evaluation, while the others maintained a qualitative macroscopic evaluation. In histological analysis, on average, pancreases transported in the active-cooling container demonstrated better tissue quality by presenting more preserved cellular structures. Conclusion: The preclinical experimental model demonstrated that, although the organ was kept within the recommended temperature range, organs maintained in the technological solution EMAIS-SR, which does not use ice, were better preserved. Furthermore, the only case in which temperature exceeded the recommended limit, that is, in which the organ warmed after packaging, occurred in the traditional ice-filled container. The research encourages the development of new and more robust studies on clinical decisions regarding safe thermal limits and best practices for transporting pancreases intended for transplantation.